DESIGN AND DEVELOPMENT OF RECRUITMENT APPLICATION AND SELECTION OF EMPLOYEES BASED ON COMPETENCE IN RSIA PUTRI SURABAYA - Mirza, Kamanda Satio; Maulana, Yoppy Mirza; Sunarto, M.J Dewiyani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Putri Hospital Surabaya is a company or institution that specializes in health especially in pregnant and childbirth care that rescue at Arief Rahman Hakim Street, Surabaya. In its business process Putri Hospital has the employee resource needs of approximately 179 employees divided into 21 sections. In fulfilling the needs of these employees and apply one mission of RSIA Putri Surabaya is "Providing professional services and high quality", then every once or every year precisely in March or September carried out the implementation of recruitment and selection of employees. To assist the HRD staff in the process of recruitment and selection of new employees, then built application-based recruitment and employee-based website. The process of recruitment and selection of employees in the application using competency standards tailored to the needs of the company to get qualified and competent candidates. The result of this research will produce recruitment and employee selection application at Putri Hospital Surabaya. This application can help the process of recruitment and selection of employees so that the process can be more quickly and can more precisely in getting qualified and competent employees. This application is also built based on the website so it can run online.